High-mechanical-strength super-thick electrode based on 3D printing technology and preparation method

Preparation of ultra-thick, low curvature orientation structure electrodes through 3D printing technology and in-situ refrigeration technology, solving the problem that traditional methods are difficult to improve the electrode thickness and mechanical stability, and achieving high mechanical strength and electrochemical stability electrodes, suitable for microelectronics Devices and other applications.

CN119480889APending Publication Date: 2025-02-18SOUTHEAST UNIV
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411595338.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Traditional ink casting methods are difficult to improve electrode thickness or achieve geometric complexity, resulting in insufficient mechanical stability and energy density of batteries, especially in microelectronics applications.

Method used

Using 3D printing technology and combined with in-situ cryogenic freezing technology, ultra-thick, low curvature orientation structure electrodes are designed and printed, and the mechanical strength and electrochemical performance of the electrodes are enhanced through directional hole structure and multi-scale design.

Benefits of technology

The high mechanical strength and electrochemical stability of the electrode are achieved, which can effectively resist external stress and alleviate the volume changes of the electrode material, and improve the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119480889A_ABST
    Figure CN119480889A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of battery energy storage devices, in particular to a preparation method of a high-mechanical-strength super-thick electrode based on a 3D printing technology. Firstly, an electrode active material is mixed with a conductive agent, an adhesive and a solvent according to a certain mass ratio to prepare printing electrode ink; and then, filling the ink into a direct writing type 3D printer, designing and printing a thick electrode with controllable layer number on a copper plate soaked in liquid nitrogen for treatment by adopting an in-situ freezing technology as an assistance, and finally obtaining the high-mechanical-strength thick electrode with a directional hole structure on the microscopic scale through post-treatment such as freeze drying and the like. According to the method, an ultra-thick electrode with the thickness exceeding 2.5 mm can be manufactured, and therefore the ultra-high area capacity is achieved. Due to the fact that the micro-channel in the vertical direction is formed, the 3D printed super-thick electrode has the remarkable compression resistance, and the high compression modulus larger than 2 MPa can be provided. The method for preparing the high-mechanical-stability super-thick electrode through the directional freezing assisted 3D printing technology is low in cost, easy and convenient to operate and wide in application range and has great application potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery energy storage devices, and in particular to a method for preparing an ultra-thick electrode with high mechanical strength based on 3D printing technology. Background Art

[0002] Batteries are known for their high energy density, long life, and low cost, making them a widely used energy storage system. However, the continuous demand for improved energy density and mechanical stability remains a major challenge as progress in increasing electrode thickness or achieving geometric complexity through traditional ink casting methods is limited. Compared with 2D thick electrodes, 3D structures have significant advantages in ion and electron pathways and electrode integrity. Therefore, rational design and construction of 3D electrodes with high mass loading is a good solution to balance energy density and power density.

[0003] Advanced 3D printing technologies, such as ink direct writing printing, control the deposition process through computer-aided design software and realize the rapid construction of various layer-by-layer electrode structures. However, as the thickness of the electrode increases, the mechanical properties of the 3D printed thick electrode degrade, which in turn affects the electrochemical performance of the battery. In addition, the compression modulus of most 3D printed electrodes reported so far is below the MPa level. Therefore, the rational design, optimization and precise control of the structure of 3D printed electrodes are of great significance to improving the mechanical stability of high energy density batteries.

[0004] In order to improve the mechanical strength of the electrode, inspired by the low-curvature structure, the use of highly oriented bamboo structures has the potential to improve the toughness of the electrode. Although the currently reported ice templates, wood templates and magnetic field-induced alignment techniques can effectively construct low-curvature oriented structure electrodes. However, the electrodes constructed by these preparation methods are structurally limited and cannot be used in specific environments, such as microelectronic devices, which makes it impossible for batteries constructed based on the above electrode preparation methods to be more widely used. 3D printing technology can meet the macroscopic design of electrode structures and significantly increase the thickness of electrodes, but the complex microscopic structure of electrodes is difficult to control. Therefore, how to prepare low-curvature oriented structure electrodes with microscopic high directional arrangement through 3D printing technology, greatly improve the mechanical strength of electrodes, and apply them to microelectronic devices is still a challenge. Summary of the invention

[0005] The purpose of the present invention is to propose a method for preparing ultra-thick electrodes with high mechanical strength based on 3D printing technology in response to the problems existing in the background technology. The 3D printing method for preparing battery electrodes proposed in the present invention is novel, simple in process, low in cost, and can realize the arbitrary multi-scale geometry and microstructure of electrodes, which has important application value for developing ultra-thick low-curvature directional structure electrodes with high energy density, high mechanical and electrochemical stability.

[0006] The technical solution of the present invention is a method for preparing an ultra-thick electrode with high mechanical strength based on 3D printing technology, comprising the following specific steps:

[0007] S1, mixing the battery electrode active material, the conductive agent, the binder and the solvent in a certain mass ratio, and stirring and grinding them to prepare the printing electrode ink;

[0008] S2, loading the printed electrode ink into an ink direct writing 3D printer, using in-situ freezing technology as an aid, designing and printing on a copper plate treated in liquid nitrogen;

[0009] S3, design and print electrodes with different numbers of layers and shapes;

[0010] S4, freeze-drying the printed electrode to obtain an ultra-thick low-curvature oriented structure electrode with a oriented pore structure;

[0011] The thickness of the prepared ultra-thick low-curvature directional structure electrode can exceed 2.5 mm. Due to the existence of the directional pore structure, its compression modulus is much higher than the currently reported non-directional structure thick electrode (less than 1 MPa). This makes the prepared ultra-thick low-curvature directional structure electrode have higher mechanical stability. This mechanical stability is mainly reflected in that it can not only effectively resist external stress, but also alleviate the volume change of the electrode material during the cycle, thereby improving battery performance.

[0012] Preferably, the battery electrode active material in S1 includes a positive electrode material and a negative electrode material;

[0013] The positive electrode material is selected from one of lithium iron phosphate, lithium manganese oxide, lithium nickel cobalt manganese oxide, sodium vanadium phosphate or sulfur-carbon composite electrode;

[0014] The negative electrode material is selected from one of graphite, hard carbon, soft carbon, lithium titanate, silicon, silicon dioxide or cobalt tetroxide.

[0015] Preferably, the conductive agent in S1 is selected from few-layer graphite, carbon nanotubes, graphene, carbon black or a combination thereof.

[0016] Preferably, when the solvent in S1 is deionized water, the binder is selected from cellulose nanofibers, sodium alginate, chitosan, polyvinyl alcohol, polyacrylic acid or a combination thereof.

[0017] Preferably, in S1, when the solvent is an organic solvent N-methylpyrrolidone NMP or dimethyl sulfoxide DMSO, the binder is selected from polyvinylidene fluoride PDVF, polyvinylidene fluoride-hexafluoropropylene PDVF-HFP, polymethyl methacrylate PMMA or a combination thereof.

[0018] Preferably, the mass ratio of the active material, the conductive agent and the binder in S1 is 1-9:0.25-5:0.25-5.

[0019] Among them, conversion active materials such as sulfur-carbon composite positive electrode, silicon, silicon dioxide, cobalt tetroxide negative electrode, etc., have low conductivity, which will affect the charge and discharge performance of the battery, and the low proportion of active materials will lead to a low electrode area capacity; different conductive agents have different specific surface areas, which will affect the mechanical properties of the electrode, specifically manifested as fragility, powdering and falling off from the surface of the current collector, and low carbon content will also lead to poor electrode conductivity and poor electrochemical performance; different matching ratios of binders and solvents will affect the viscosity of the slurry, and then affect the surface wettability of the electrode, and finally lead to different freeze-drying or heat drying effects, and too high a binder content will lead to poor electrode conductivity and poor electrochemical performance, while too low a binder content will easily lead to loose electrode bonding and poor mechanical properties.

[0020] Preferably, the ink slurry in S1 is stirred using a magnetic stirrer for 1 to 12 hours to be fully mixed, or manually ground for 20 minutes to 2 hours, or stirred for 10 minutes to 1 hour using a stirring-degassing machine, and then degassed for 10 minutes to 1 hour;

[0021] The liquid / solid ratio of the electrode ink is in the range of 1 to 10:1 mL / mg.

[0022] Preferably, the nozzle diameter of the ink direct writing 3D printer in S2 is 20 to 1000 μm, the printing pressure is 5 to 100 psi, the needle speed is 1 to 50 mm / s, and the layer height is consistent with the nozzle diameter;

[0023] The printed shape and structure are modeled using 3D software and sliced ​​and imported into the printer system for use. The diameter of the circular electrode is between 10 and 19 mm, the side length of the square electrode is between 1 and 5 cm, and the thickness of all electrodes is controlled below 2 cm.

[0024] Preferably, the temperature of the copper sheet after immersion in liquid nitrogen in S2 ranges from -100°C to -10°C; the copper sheet is set at a certain tilt angle, including 0°, 15°, 30°, 45°, and 60°. The copper sheet without a tilt angle has a temperature gradient only in the Z-axis direction, while the copper sheet with a tilt angle also has a temperature gradient in the XY plane. This dual temperature field can improve the uniformity of the pore direction and pore morphology of the unidirectional frozen sample.

[0025] Preferably, the freeze-drying time in S4 is 1 to 24 hours, and the freeze-drying temperature is -10 to -50°C.

[0026] Compared with the prior art, the present invention has the following beneficial technical effects:

[0027] 1. Excellent compression resistance and electrochemical performance: Compared with traditional planar battery electrodes, the high mechanical strength, ultra-thick, low-curvature directional structure electrode prepared by the 3D printing technology proposed in the present invention can resist external stress and alleviate the volume expansion of the electrode material during the cycle while maintaining good electrochemical performance.

[0028] 2. Simplified process and low cost: The present invention provides a 3D printing method assisted by directional freezing technology, which has a simple process, low cost and is suitable for mass production.

[0029] 3. Realization of ultra-thick electrodes: Ultra-thick battery electrodes are prepared simply and efficiently through ink direct writing 3D printing.

[0030] 4. Optimized microstructure: Using the vertical microchannels of the tree's internal structure as a low-curvature directional structure model, combined with directional freezing technology, the preparation of the electrode's microporous structure is achieved, which can shorten the ion transmission distance, promote ion transmission and adapt to volume changes, and improve the electrochemical performance of the battery. The directional microstructure enhances the mechanical properties of the 3D printed electrode, giving it the toughness of a tree.

[0031] 5. Adjustable macroscopic geometric structure: The electrode prepared by the method of the present invention has an adjustable macroscopic geometric structure, which can realize different functions. Printing a macroscopic impact-resistant structure, such as a Bouligand structure, can further enhance the mechanical properties of the electrode; printing an interdigitated microstructure can be applied to micro batteries; printing a larger and thicker square electrode can be used for soft-pack batteries.

[0032] 6. Adjustable microporous structure: By adjusting the ratio of raw materials, ink concentration, copper sheet inclination angle, directional freezing temperature and drying time, the electrode prepared by the method of the present invention has an adjustable microporous structure, which can change the number and size of the microporous structure distribution. The electrochemical and mechanical properties of the electrode can be improved by regulating the microporous structure.

[0033] 7. Wide applicability: The electrode preparation method proposed in the present invention is also applicable to the preparation of electrodes for other energy storage systems. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is a microscopic SEM image of the 3D printed ultra-thick low-curvature directional structure electrode;

[0035] Figure 2 This is a diagram showing the different number of layers of 3D printed ultra-thick low-curvature directional structure electrodes;

[0036] Figure 3 This is the SEM image of the 3D printed ultra-thick low-curvature directional structure electrode at an ink concentration of 3mL / mg;

[0037] Figure 4 Compression performance test diagram of 3D printed ultra-thick low-curvature directional structure electrode and non-directional electrode;

[0038] Figure 5 Electrochemical performance diagram of 3D printed ultra-thick low-curvature directional structure electrode.

[0039] Figure 6 Actual photo of a soft-pack full-battery extrusion-powered battery with 3D-printed ultra-thick, low-curvature directional structure electrodes.

[0040] Figure 7 The loading diagram of 3D printed ultra-thick low-curvature directional structure electrode at different thicknesses. DETAILED DESCRIPTION

[0041] Example 1

[0042] A high mechanical strength ultra-thick electrode prepared based on 3D printing technology, the preparation method thereof comprises the following steps:

[0043] 1. Mix micron silicon powder, carbon black and sodium alginate in a mass ratio of 5:2.5:2.5, add deionized water to make the liquid-solid ratio reach 4mL / mg, then stir for 10min and then degas for 10min in a stirring-degassing machine to prepare printing electrode ink.

[0044] 2. The printed electrode ink was loaded into a direct-write 3D printer with a nozzle diameter of 400 μm, a printing pressure of 20 psi, and a needle speed of 10 mm / s, and in-situ cryo-printing was performed on a flat copper plate (-80°C, 0°) soaked in liquid nitrogen.

[0045] 3. Print a grid-filled circular electrode with a diameter of 12 mm and freeze-dry for 10 h at -40 ° C. Change the number of printed layers to control the electrode thickness and active material loading.

[0046] 4. Obtain a low-curvature directional structure electrode with a microscopic directional pore structure.

[0047] 5. SEM images of low curvature oriented structure electrodes Figure 1 shown.

[0048] Example 2

[0049] A high mechanical strength ultra-thick electrode prepared based on 3D printing technology, the preparation method thereof comprises the following steps:

[0050] 1. Mix lithium nickel cobalt manganese oxide (NCM811), PVDF, and few-layer graphite in a mass ratio of 8:1:1, add an appropriate amount of NMP, and grind manually to a suitable viscosity to prepare printing electrode ink.

[0051] 2. Load the printed electrode ink into a direct writing 3D printer with a nozzle diameter of 400 microns, a printing pressure of 30 psi, and a needle speed of 20 mm / s, and perform in-situ cryoprinting on an angled copper plate (-10°C, 15°) soaked in liquid nitrogen. It is intended to reduce the growth rate of ice crystals by increasing the temperature. The slower the growth rate, the larger the low-curvature directional structure pores and the fewer the number of pore wall layers.

[0052] 3. Print the Bouligand structure electrode with a diameter of 19 mm and a thickness of 2 mm, and freeze-dry it for 8 hours at a temperature of -30 °C.

[0053] 4. Obtain a multi-scale low-curvature directional structure electrode with a microscopic directional pore structure and a macroscopic impact-resistant Bouligand structure.

[0054] Example 3

[0055] A high mechanical strength ultra-thick electrode prepared based on 3D printing technology, the preparation method thereof comprises the following steps:

[0056] 1. The sulfur-carbon composite powder, graphene, and cellulose nanofibers were mixed in a mass ratio of 7:2:1, and deionized water was added to make the liquid-solid ratio reach 3 mL / mg. Then, the mixture was stirred for 20 min and then degassed for 10 min in a stirring-degassing machine to prepare a printed electrode ink.

[0057] 2. Load the printed electrode ink into a direct writing 3D printer with a nozzle diameter of 200 microns, a printing pressure of 20 psi, and a needle speed of 15 mm / s, and perform in-situ cryoprinting on a flat copper plate (-100 to -10°C, 30°) soaked in liquid nitrogen. It is intended to change the growth rate of ice crystals by changing the temperature, thereby changing the pore structure morphology.

[0058] 3. Print different layers of interdigitated microelectrodes with a length of 1 cm and a width of 0.5 cm, and freeze-dry for 10 hours at a temperature of -40°C.

[0059] 4. Obtain interdigitated microelectrodes with controllable thickness.

[0060] 5. Photos of interdigital microelectrodes with controllable thickness Figure 2 shown.

[0061] Example 4

[0062] A high mechanical strength ultra-thick electrode prepared based on 3D printing technology, the preparation method thereof comprises the following steps:

[0063] 1. Mix different positive and negative electrode materials, carbon nanotubes, and polyvinyl alcohol in a mass ratio of 7:2:1, add deionized water to make the liquid-solid ratio reach 3mL / mg, and then stir at 90°C for 3h in a heating mixer to prepare printed electrode ink.

[0064] 2. The printed electrode ink was loaded into a direct-write 3D printer with a nozzle diameter of 200 μm, a printing pressure of 20 psi, and a needle speed of 15 mm / s, and in-situ cryo-printing was performed on a flat copper plate (-80°C, 0°) soaked in liquid nitrogen.

[0065] 3. Print thick electrodes of different shapes and different electrode materials, with the thickness controlled to about 2 mm, and freeze-dry for 10 hours at a temperature of -40°C.

[0066] 4. Obtain 2 mm thick electrodes with different material properties and different shapes.

[0067] Example 5

[0068] A high mechanical strength ultra-thick electrode prepared based on 3D printing technology, the preparation method thereof comprises the following steps:

[0069] 1. Lithium titanate, carbon black-graphene, sodium alginate-chitosan were mixed in a mass ratio of 7:2:1, deionized water was added to make the liquid-solid ratio reach 3mL / mg, and then stirred in a stirring-degassing machine for 20 minutes and then degassed for 10 minutes to prepare printing electrode ink. The ratio of the composite carbon material and the binder material was adjusted according to the rheological properties of the ink, which ultimately affected the printing process and the electrochemical and mechanical properties of the electrode.

[0070] 2. The printed electrode ink was loaded into a direct-write 3D printer with a nozzle diameter of 200 μm, a printing pressure of 20 psi, and a needle speed of 15 mm / s, and in-situ cryo-printing was performed on a flat copper plate (-80°C, 0°) soaked in liquid nitrogen.

[0071] 3. Print different layers of interdigitated microelectrodes with a length of 1 cm and a width of 0.5 cm, and freeze-dry for 10 hours at a temperature of -40°C.

[0072] 4. Obtain interdigitated microelectrodes with adjustable ink rheological properties and controllable thickness.

[0073] Example 6

[0074] A high mechanical strength ultra-thick electrode prepared based on 3D printing technology, the preparation method thereof comprises the following steps:

[0075] 1. Mix silica, carbon black, and cellulose nanofibers in a mass ratio of 5:3:2, add deionized water to make the liquid-solid ratio reach 3.5 mL / mg, and then stir for 15 min and degas for 5 min in a stirring-degassing machine to prepare printing electrode ink.

[0076] 2. Load the printed electrode ink into a direct-write 3D printer with a nozzle diameter of 200 to 400 μm, a printing pressure of 40 psi, and a needle speed of 15 mm / s, and perform in-situ cryo-printing on a flat copper plate (-80°C, 0°) soaked in liquid nitrogen.

[0077] 3. Print a seven-layer circular electrode with a diameter of 14 mm and freeze-dry it for 10 hours at a temperature of -40°C.

[0078] 4. Obtain a circular electrode with controllable thickness.

[0079] The performance of the electrodes prepared in Examples 1-6 was tested.

[0080] Electrode compression resistance test steps:

[0081] The electrodes printed out in Examples 1-6 were subjected to mechanical property tests by a universal testing machine. The working distance of compression was calibrated by the thickness of the electrode, the compression speed was 3 mm / min, the maximum applied pressure was 500 N, and the compressive stress-strain curve data of all types of electrodes were tested and recorded ten times, and the average value was taken after the compression modulus was calculated; in order to simulate the environment of the electrode in the electrolyte, an appropriate amount of commercial electrolyte was added to each type of electrode, and the compression resistance of the electrode was tested, and the test method was the same as above. Further, finite element analysis (FEA) was carried out using finite element software to study the structural changes of the directional low-curvature directional structure under external stress. Using actual heavy objects, such as weights (1 to 10 kg), load them on the upper side of the low-curvature directional structure thick electrode to observe the structural integrity of the electrode after compression.

[0082] Electrochemical performance test steps:

[0083] Half-cell assembly: The printed low-curvature directional structure thick electrode and commercial lithium foil are directly used as positive and negative electrodes, the separator is Celgard 2500, and the electrolyte is an ester electrolyte. The button cell is assembled in a glove box filled with argon and sealed with a hydraulic crimper; the electrochemical data of the battery is collected using the LAND battery test system. The full battery is assembled by matching different positive and negative electrodes. In terms of surface capacity control, the negative electrode capacity is slightly higher than the positive electrode capacity. The assembly of the soft-pack full battery is encapsulated by aluminum-plastic film.

[0084] The test results are shown in the following table:

[0085] Table 1 Example parameters and electrode performance

[0086]

[0087]

[0088] Analysis of the experimental data in Table 1 shows that the compression capacity test of the electrode can show a maximum compression modulus of more than 3MPa. A 2kg weight was applied to the top of the electrode, and the electrode was not damaged after compression. Finite element analysis of the electrode showed that when the applied force was parallel to the direction of the directional hole, the stress distribution of the electrode was uniform; on the contrary, when the external force was applied to the local structure of the non-directional electrode, obvious stress concentration occurred. This shows that the electrode prepared by this method can resist the influence of external forces.

[0089] In Example 1, a micron silicon negative electrode was used, which as an electrode material has a large volume expansion during the charge and discharge process. The electrochemical performance of electrodes with different numbers of layers showed a behavior independent of thickness, which indicates that the internal stress of silicon volume change has been released, indicating that the electrode prepared by this method can achieve the slow release of internal stress.

[0090] The system used in Implementation Case 2 is an oily ink system, which cannot achieve in-situ freezing, so the mechanical properties are poor, but the thick electrode significantly improves the surface capacity.

[0091] The partial crushing of the material in the compression test in Implementation Case 3 can be attributed to the excessively high proportion of carbon material in the sulfur-carbon composite material, the excessively large specific surface area, and the detachment of the material under external stress. The pore structure morphology obtained at -50°C is the most uniform and elongated, which is conducive to the improvement of mechanical and electrochemical properties.

[0092] The low-curvature oriented structural pore structure regulation effect of the binder polyvinyl alcohol used in Implementation Case 4 is poor, far inferior to the sodium alginate and cellulose nanofiber system, and therefore the mechanical properties are poor.

[0093] In implementation case 5, a composite carbon material is used to improve the electrochemical performance, and a composite binder is used to improve the mechanical properties of the electrode, so the performance is better.

[0094] In implementation case 6, a cellulose nanofiber binder with good mechanical properties was used, which not only ensured the electrochemical performance but also significantly improved the mechanical properties of the electrode.

[0095] like Figure 3 As shown, based on implementation case 1, by adjusting the concentration of the ink to 3 mL / mg, the pore structure of the printed electrode with low curvature directional structure is significantly reduced, proving that the electrode prepared by the method of the present invention has an adjustable microporous structure and can change the number and size of the microporous structure distribution.

[0096] like Figure 4 As shown, the oriented microchannel electrode (D-3DP) prepared by Example 1 has a thickness of up to 2.7 mm and a compression modulus of up to 2.77 MPa, while the non-oriented electrode (N-3DP, the copper sheet is at room temperature during printing) has a compression modulus of only 0.58 MPa.

[0097] like Figure 5 As shown, a directional microchannel electrode (D-3DP) was prepared by implementing Case 1, and its electrochemical cycling performance was compared with that of a non-directional electrode (N-3DP) and a coated electrode (2DC). The results showed that the surface capacity retention rate of D-3DP was as high as 89% in 100 cycle tests.

[0098] like Figure 6 As shown, by assembling a directional low-curvature directional structured micron silicon||NCM811 soft-pack full battery, the battery is squeezed as a whole with fingers, and the battery works normally and continuously supplies energy to the LED lamp, indicating that the electrode prepared by the method of the present invention has excellent mechanical stability while ensuring high electrochemical performance.

[0099] like Figure 7 As shown in the figure, by printing electrodes with different numbers of layers, the surface loading of the electrodes can be significantly increased, thereby increasing the surface capacity of the electrodes. In addition, the macroscopic and microscopic morphological structures of electrodes with different numbers of layers remain intact, proving the high quality of the ink and the reliability of the technical means.

[0100] The embodiments of the present invention are described in detail above with reference to the accompanying drawings, but the present invention is not limited thereto, and various changes can be made within the knowledge scope of technicians in the relevant technical field without departing from the purpose of the present invention.

Claims

1. An ultra-thick electrode with high mechanical strength based on 3D printing technology, characterized in that: The ultra-thick electrode comprises a battery positive electrode and a battery negative electrode; The ultra-thick electrode is an electrode having a thickness exceeding 2.5 mm and having a directional pore structure at the microscopic level; The ultra-thick electrode has high mechanical stability and can resist external stress and volume changes of the electrode material during cycling, and its compression modulus is as high as 2 MPa.

2. A method for preparing an ultra-thick electrode with high mechanical strength based on 3D printing technology, preparing the ultra-thick electrode according to claim 1, characterized in that: The specific steps include: S1, mixing the battery electrode active material, the conductive agent, the binder and the solvent in a certain mass ratio, and stirring and grinding them to prepare the printing electrode ink; S2, loading the printed electrode ink into an ink direct writing 3D printer, using in-situ freezing technology as an aid, designing and printing on a copper plate treated in liquid nitrogen; S3, design and print electrodes with different numbers of layers and shapes; S4. The printed electrode is freeze-dried to obtain an ultra-thick low-curvature directional structure electrode with a directional pore structure.

3. The method for preparing an ultra-thick electrode with high mechanical strength based on 3D printing technology according to claim 2, characterized in that: The battery electrode active materials in S1 include positive electrode materials and negative electrode materials; The positive electrode material is selected from one of lithium iron phosphate, lithium manganese oxide, lithium nickel cobalt manganese oxide, sodium vanadium phosphate or sulfur-carbon composite electrode; The negative electrode material is selected from one of graphite, hard carbon, soft carbon, lithium titanate, silicon, silicon dioxide or cobalt tetroxide; The conductive agent in S1 is selected from few-layer graphite, carbon nanotubes, graphene, carbon black or a combination thereof.

4. The method for preparing an ultra-thick electrode with high mechanical strength based on 3D printing technology according to claim 2, characterized in that: When the solvent in S1 is deionized water, the binder is selected from cellulose nanofibers, sodium alginate, chitosan, polyvinyl alcohol, polyacrylic acid or a combination thereof.

5. The method for preparing an ultra-thick electrode with high mechanical strength based on 3D printing technology according to claim 2, characterized in that: In S1, when the solvent is an organic solvent N-methylpyrrolidone NMP or dimethyl sulfoxide DMSO, the binder is selected from polyvinylidene fluoride PDVF, polyvinylidene fluoride-hexafluoropropylene PDVF-HFP, polymethyl methacrylate PMMA or a combination thereof.

6. The method for preparing an ultra-thick electrode with high mechanical strength based on 3D printing technology according to claim 2, characterized in that: The mass ratio of active material, conductive agent and binder in S1 is 1-9:0.25-5:0.25-5.

7. The method for preparing an ultra-thick electrode with high mechanical strength based on 3D printing technology according to claim 2, characterized in that: When the ink slurry in S1 is stirred, a magnetic stirrer is used to stir for 1 to 12 hours to fully mix it, or it is manually ground for 20 minutes to 2 hours, or a stirring-degassing machine is used to stir for 10 minutes to 1 hour, and then degassing for 10 minutes to 1 hour; The liquid / solid ratio of the electrode ink is in the range of 1 to 10:1 mL / mg.

8. The method for preparing an ultra-thick electrode with high mechanical strength based on 3D printing technology according to claim 2, characterized in that: The nozzle diameter of the ink direct writing 3D printer in S2 is 20-1000μm, the printing pressure is 5-100psi, the needle speed is 1-50mm / s, and the layer height is consistent with the nozzle diameter; The printed shape and structure are modeled using 3D software and sliced ​​and imported into the printer system for use. The diameter of the circular electrode is between 10 and 19 mm, the side length of the square electrode is between 1 and 5 cm, and the thickness of all electrodes is controlled below 2 cm.

9. The method for preparing an ultra-thick electrode with high mechanical strength based on 3D printing technology according to claim 2, characterized in that: The temperature of the copper sheet after immersion in liquid nitrogen in S2 ranges from -100°C to -10°C; the copper sheet is set at certain tilt angles, including 0°, 15°, 30°, 45°, and 60°.

10. The method for preparing an ultra-thick electrode with high mechanical strength based on 3D printing technology according to claim 2, characterized in that: The freeze drying time in S4 is 1 to 24 hours, and the freeze drying temperature is -10 to -50°C.

Citation Information

Patent Citations

  • Three-dimensional lithium battery preparation method based on direct writing forming 3D printing technology

    CN112186257A

  • Manufacturing method of micro lithium-sulfur battery positive electrode with any geometric structure based on 3D printing

    CN116632178A

  • 3D printing manufacturing method of miniature lithium metal negative electrode with any geometric structure

    CN117133872A

  • 3D printing high-energy-density solid-state lithium ion battery and preparation method thereof

    CN117996210A

  • MXene composite material as well as preparation method and application thereof

    CN118183957A